STAYING CONNECTED: SERVICE-USER EXPERIENCE OF THE RECOVERY JOURNEY AND LONG-TERM ENGAGEMENT WITH A MENTAL HEALTH CLINIC - Krupin, Lyuda; Todd, Nick; Howey, Eric; Perry, Tara (Canadian Social Work Review / Revue canadienne de service social, 2023)
While there has been much interest in recent years about the potential impact that short-term therapy can have on those needing mental health support, relatively little attention has been paid to the needs of those who require long-term support. In this phenomenological study exploring long-term service-users’ experiences of the recovery journey and the role of mental health support in facilitating that journey, a sample (n = 6) of service-users who had a minimum of five years of continuous involvement with a community-based mental health clinic participated in a pair of focus groups designed to help them share their experience of the recovery journey. Our analysis revealed themes of contending not just with extreme violence and other adversities, but also with an often unhelpful helping system, as service-users expended effort in locating the consistent, accessible support they needed in order to find a reason to go on in the wake of devastating personal experiences. The study also emphasized how prioritizing the top-down need for efficiency over the bottom-up need for consistent, flexible support can have the inadvertent effect of extending rather than shortening treatment. Implications of these findings for the delivery of mental health services are discussed.